Identification Soybean Processed Waste Environmental Impact and Management Alternatives (Case Study City of Jakarta Selatan) - Naomi Aurora Margareth Br. Simanjuntak; Alfiyah Najwa; Muhamad Hisyam Dhiya Ulhaq; Mutiara Octaviani; Deni Adnan; I Wayan Koko Suryawan; Nurulbaiti Listyendah Zahra (SEAS (Sustainable Environment Agricultural Science), 2021)
Processed soybeans such as tempeh and tofu are some of the foods that the people of Indonesia favour. The Tempe and Tofu processing factory produce tofu with the essential soybean ingredients as much as 17 kg every day. The tofu production process starts from soybean immersion, grinding, boiling, filtering, compaction, moulding, cutting, to frying tofu. Production activities from the tofu industry will certainly produce solid and wastewater. These wastes can have a negative impact on the environment. Therefore, the waste must be managed and treated correctly to create an environmentally friendly industry and improve environmental quality. Tofu industry waste management and treatment can be done by identifying the generation of waste that is a priority to be treated and choosing waste treatment technology. There are three alternatives for wastewater treatment from the tofu industry: the chlorine in wastewater, ponds by forming biofilms using biofilter media, and Trickling Filters.